2007
DOI: 10.1089/scd.2006.9998
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells: Molecular Targets for Tissue Engineering

Abstract: Mesenchymal stem cells (MSCs) represent an adherent, fibroblast-like population present not only in the bone marrow, but in a number of tissues, including blood, adipose tissue, muscle, and dermis. Their extensive proliferation and transdifferentiation potential makes them best suited for tissue engineering applications. Identification of growth factors and signaling pathways involved in self-renewal and differentiation is important for designing strategies to overcome replicative senescence and attain directe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
129
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(132 citation statements)
references
References 139 publications
2
129
0
1
Order By: Relevance
“…MSCs are also known as marrow stromal stem cells and marrow mesenchymal stem cells (Richardson et al 2010;Zellner et al 2010 (Satija et al 2007). In several studies, exogenous virus, or oncogene has been introduced to target the cells to construct the immortalized cells (Kelekar and Cole 1987;Arimura et al 2007;Wu et al 2007), in which the integration of target gene was random and expression of target gene might have interfered with the intracellular physiological processes, which could result in unexpected changes such as loss of differentiation characteristic and lack of control of check point.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs are also known as marrow stromal stem cells and marrow mesenchymal stem cells (Richardson et al 2010;Zellner et al 2010 (Satija et al 2007). In several studies, exogenous virus, or oncogene has been introduced to target the cells to construct the immortalized cells (Kelekar and Cole 1987;Arimura et al 2007;Wu et al 2007), in which the integration of target gene was random and expression of target gene might have interfered with the intracellular physiological processes, which could result in unexpected changes such as loss of differentiation characteristic and lack of control of check point.…”
Section: Discussionmentioning
confidence: 99%
“…Self-renewal is an intrinsic property of stem cells that allows them to give rise to non-differentiated daughter cells by proliferating, preventing apoptosis, and avoid lineage commitment (5,6). This process is important for the maintenance of a stem cell pool that, in the case of MSCs, can exert a more robust effect within the context of a wound.…”
mentioning
confidence: 99%
“…This process is important for the maintenance of a stem cell pool that, in the case of MSCs, can exert a more robust effect within the context of a wound. Although several cytokines, growth factors, adhesion molecules, and extracellular matrix components have been identified as cues that signal MSCs to differentiate, the molecular signals that modulate MSC self-renewal remain unknown (5). Data from the hematopoietic stem cell (HSC) field have documented the involvement of Wnt, Notch, and BMP signaling cascades in self-renewal; these pathways are implicated in the expansion of undifferentiated HSCs that upon transplantation into lethally irradiated mice successfully reconstitute the cleared bone marrow (7)(8)(9).…”
mentioning
confidence: 99%
“…Differentiation of MSCs is an ordered process that proceeds stepwise through cell proliferation, differentiation, formation of extracellular matrix and mineralization stages (Marie and Fromigue 2006;Satija et al 2007). Kulterer et al (2007), using an oligonucleotide microarray-based gene expression analysis, demonstrated a specific time scale for the in vitro differentiation of BM-MSCs: proliferation phase (0-4 days), matrix maturation phase (4-14 days) and mineralization phase (14-21 days).…”
Section: Discussionmentioning
confidence: 99%